The Eph receptor family - Pasquale, Elena (Henry Stewart Talks, 2007)
Members of the Eph receptor and ephrin ligand families and specificity of binding interactions, Domain structure of Eph receptors and ephrins, Eph receptor-ephrin interactions, Dimerization, tetramerization and further clustering in Eph-ephrin signaling, Tyrosine phosphorylation in Eph-ephrin activation, Modes of signal termination, Eph-ephrin signaling pathways affecting the actin cytoskeleton and cell adhesion: Cell repulsion versus adhesion/attraction, pathways that are activated downstream of Eph receptors, Main Eph effects on cell behavior: shaping and positioning cellular processes and cell migration, Eph receptors in topographic mapping in the visual system, Eph receptors in the organization of axonal projections, Eph receptors in angiogenesis and lymphangiogenesis, Eph receptors in stem cell proliferation and differentiation, Eph receptors in cancer, Eph receptors as drug targets
Reviewed at 2017/05/06